Peran PBB dalam Menanggulangi Bride Kidnapping Non Konsensual di Kirgistan - Sari, Anggun Putri Kemuning; Parameswari, Anak Agung Ayu Intan; Sushanti, Sukma (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 4 No 2 (2024): JURNAL DIKSHI, 2024)
This study examines the role of the United Nations in tackling non-consensual Bride Kidnapping in Kyrgyzstan with a time locus of 2020-2021. This paper examines the role played by the United Nations as an international organization which has 3 main roles, such as an instrument, arena and actor. Based on secondary data sources, researcher found a correlation between the United Nations through the 6 pillars of the global spotlight initiative in dealing with non-consensual Bride Kidnapping in Kyrgyzstan with the main role of international organizations and their functions and powers. Among the 3 main roles that the UN has, this article concludes that the role used by the UN as an international organization is an instrument and actor through the 6 pillars of the global spotlight initiative namely law and policy, data, institutions, services, prevention and change of norms, and women's social movements . Keywords : Bride Kidnapping, Global Spotlight Initiative, Kyrgyzstan, United Nations (UN)